Penggunaan Teknologi Big Data untuk Analisis Prediksi Bisnis - Farah Ananda Lubis; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
The use of big data and business analytics provides benefits to businesses globally. This research focuses on business analytics and big data technologies to improve business decision-making processes, technical approaches, applications, and research questions. Especially in the era of data explosion, “data” is very important. Therefore, those who have the ability to process and use multifaceted data sets can gain several benefitsThree things differentiate big data: volume, velocity, and variety.Understanding client questions requires a strong understanding of data. Producing extraordinary new products and services is essential. Accessible platforms include Hadoop, MongoDB, Cassandra, Apache Spark, and Xplenty, which can be used to store and process very large amounts of data and have the capacity to store and process very large data, and are used as supporting tools to increase utilization and saving resources, reducing calculation time and effort, and enabling better business decisions. Big data includes technologies and plans that involve data that is rapidly changing, diverse, or so large that managing it with traditional technologies, capabilities, and infrastructure is a challenge Indonesia is becoming a commercial user of big data.